Perbedaan Tingkat Perkembangan Sosial Anak Obesitas dan Tidak Obesitas pada Usia Sekolah di Sekolah Dasar Katolik Maria Fatima Jember (The Difference Level of Social Development of Obese and Non-Obese Childhood at School Age in Elementary School Katolik M - Arif Hidayatullah; Lantin Sulistyorini; Rondhianto Rondhianto (Pustaka Kesehatan, 2015)
Obesity has become a serious problem in developing countries at this time. Obesity is a condition of excess fat due to an imbalance of inputs and energy use. Obesity in children has an impact on child development, especially in the physical and psychosocial aspects. Social development is one of the important aspects of child development at school age. The purpose of this research was an analyzed the differenced level of social development of obese and non-obese childhood at school age in elementary school Katolik Maria Fatima Jember. Design of this research was descriptive analytic by using cross sectional. Method of collecting samples by using simple random sampling. Data were analyzed by using Mann Whitney (α=0,05). The result of statistic test showed that p value=0.000 (p value ≤ 0,05), that mean a significant differences level of social development of obese and non-obese childhood at school age in Elementary School Katolik Maria Fatima Jember. Pediatric nurse is one of the health services should be able to improve the health of children by pressing the prevalence of obese children in Indonesia and deliver information to teachers and parents about the importance of child development, especially social development of childhood.   Keywords: obesity, child development, social development.